PENYULUHAN KESEHATAN DAN SKRINING PEMERIKSAAN KOLESTEROL DAN ASAM URAT PADA LANSIA - Harianja, Edison; Marsudi, La Ode (Program Studi Teknologi Laboratorium Medis, ITKES Wiyata Husada Samarinda, 2022)
Cholesterol is a steroid found in body tissues, a structural part of all cell membranes, and plays important roles such as being a precursor to various compounds such as bile acids, steroid hormones, and vitamin D. Cholesterol is obtained from synthetic processes in the body, especially the liver, adrenal cortex, intestines, and kidneys reproductive tissue (endogenous cholesterol), and from foods containing cholesterol such as egg yolks, meat, liver, and brain (extrinsic cholesterol). The increase in cholesterol levels is suspected to be caused by the consumption of foods that contain high cholesterol and low physical activity. Increased uric acid in the blood can be caused by the consumption of foods that have high purine levels, generally, these foods are foods that contain high protein levels. This community service aims to make the public know and understand how to detect uric acid early, as well as the impact of high uric acid in adulthood caused in order to achieve a productive and healthy society.